THE ANALYSIS OF FINANCIAL RATIO OF GROWTH PROFIT WITH COMPANY SIZE AS A VARIABLE MODERATING IN COMPANIES CONSUMER GOODS WHO ARE REGISTERED IN INDONESIA STOCK EXCHANGE - Simamora, Meilanny (International Journal of Public Budgeting, Accounting and Finance, 2018)
This study aimed to analyze the influence of Current Ratio, Debt to Asset Ratio, Inventory Turn Over, Total Asset Turn Overand Sales Growth on Growth L aba with U kuran C ompany as moderating variable in the consumer goodscompany listed on the Indonesia Stock Exchange. Observation period is 2013 to 2017 with a total sample of 24 companies. The analytical method uses multiple linear regression analysis of panel data models and a moderating variable testing model with residual test.             The results showed that CurrentRatio  and Partial Sales Growth has a negative effect on Profit Growth, while Debt to Asset Ratio, Turn Over Inventoryand Total Asset Turn Overpartially positive effect on profit growth. Company Size tida k can moderate the influence of Current Ratio, Debt to Asset Ratio, Inventory Turn Over, Total Asset Turn Overand Sales Growth on Profit Growth.